PELAKSANAAN FUNGSI TUNGKU TIGO SAJARANGAN BERDASARKAN PERATURAN DAERAH NOMOR 7 TAHUN 2018 TENTANG NAGARI DI KENAGARIAN TANJUNG BONAI KECAMATAN LINTAU BUO UTARA KABUPATEN TANAH DATAR TAHUN 2021 - Ridwanul Fajri; Isril ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Tungku Tigo Sajarangan is a form of leadership in Minangkabau. Tungku Tigo Sajarangan consisting of niniak mamak, alim ulama and cadiak pandai is an formal leadership in the governance system of West Sumatera. With the rapid development of the times, this Tungku Tigo Sajarangan must carry out its duties and functions in protecting the future of Minangkabau culture and Nagari Citizens. This study aims to determine the implementation of the function of the Tungku Tigo Sajarangan in the village the implementation of the function of the Tungku Tigo Sajarangan in Tanjung Bonai District Noeth Lintau Buo District is not going well. This happened due to several factors such as the lack of support from the Nagari Government and the lack of collaboration between the Nagari Government and a traditional institution called Kerapatan Adat Nagari (KAN).of Tanjung Bonai Lintau Buo Utara District and to find out what factors hinder the implementation of the function on Tungku Tigo Sajarangan. This research uses descriptive research type. Data collection techniques are observation, interviews and documentation. The data analysis technique in this study was carried out qualitatively. The results of the study explain that Keywords : Tungku Tigo Sajarangan, Democration, Elite, Function